Rozwój przepisów prawnych w zakresie bioindykacji środowiskowej a stan jakości wód jeziorowych - Zębek, Elżbieta; Napiórkowska-Krzebietke, Agnieszka (Studia Prawnoustrojowe, 2019)
This article shows the genesis of legal regulations in the range of environmental bioindication in national legislation as a result of the implementation of EU solutions. The most important legal act in EU is the Framework Water Directive while the Water Law of 2017 in Poland. The main purpose of these legal acts is to maintain a good status, especially ecological status or potential of water bodies based on bioindication. Changes in this area contributed to detailing and standardizing of the biological indicators of waters, which allow for a more detailed examination of the status of waters and defning the directions of their protection. The assessment of water quality in Warmian-Mazurian Voivodship indicates that approximately 30% of the lakes studied in 2010–2017, had at least good ecological status or potential. In 70% of the lakes, primarily phytoplankton (the most sensitive bioindicator) decided on lowering to below good ecological status/potential. Recently, the fnal assessment of the status (ecological plus chemical) of water bodies has been more rigorous due to chemical status based on exceeded content of priority substances in fsh (i.e. in another important bioindicator)